Islamic Law and Indonesian Society: A Study on the Characteristics of Islamic Law in Indonesia - Bisri, Hasan (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to elaborate on philosophical perspectives on Islamic law and Indonesian society. The focus of this study is a philosophical view on the characteristics of Islamic law in Indonesia. This study uses a critical review method (critical review) of several primary and secondary literature on Islamic law, Islamic legal philosophy, and the development of Islamic law in Indonesia. Through this critical study, I endeavor to elaborate on the principles and essential characteristics of Islamic law and then reflect it into the Indonesian context. The nature and characteristics of Indonesian Islamic law are philosophically in harmony with the world view and attitude of Indonesian human life. Islamic law in Indonesia and the Indonesian people have the same characteristics, trying to eliminate difficulties, narrowness, and shortsightedness. Both tend to be open, tolerant, and respectful of all God’s creatures. Both have the same view of the burden of life. Humans should only be burdened according to their abilities. They tend to have the same perception of tajarrud. Both of them want to realize the benefit of as many people as possible, realize equitable justice, prevent crime, and uphold the values of humanity, humanization, ethics, morals, and social welfare.